2019
DOI: 10.1029/2018wr023896
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reforestation of a Degraded Imperata Grassland on Dominant Flow Pathways and Streamflow Responses in Leyte, the Philippines

Abstract: Reforestation of degraded grasslands can increase the soil hydraulic conductivity and number of preferential flow pathways. However, it is not clear to what extent these changes affect streamflow responses and whether this depends on the event size. We, therefore, studied the hydrological response of two small catchments near Tacloban, Leyte (the Philippines): a degraded Imperata grassland catchment and a catchment that was reforested 23 years prior to our study. Precipitation, stream stage, and electrical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…In a land use change context, Ziegler et al (2007) and Chaves et al (2008) also observed overland stormflow in a Vietnamese and a Brazilian catchment, respectively, with a clear increase of surface runoff generation after forest clearance compared to pasture and forest. Recently, van Meerveld et al (2019) reported a slowing of surface runoff generation with forest recovery in a Philippine catchment. Similar to our results, lateral sub‐surface runoff generation and zero surface flow were observed in tropical rainforest catchments on more permeable volcanic substrates such as in Mexico (Muñoz‐Villers & McDonnell, 2012) and Puerto Rico (Scholl et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a land use change context, Ziegler et al (2007) and Chaves et al (2008) also observed overland stormflow in a Vietnamese and a Brazilian catchment, respectively, with a clear increase of surface runoff generation after forest clearance compared to pasture and forest. Recently, van Meerveld et al (2019) reported a slowing of surface runoff generation with forest recovery in a Philippine catchment. Similar to our results, lateral sub‐surface runoff generation and zero surface flow were observed in tropical rainforest catchments on more permeable volcanic substrates such as in Mexico (Muñoz‐Villers & McDonnell, 2012) and Puerto Rico (Scholl et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Much research has examined the impacts of land use changes on hydrological processes in the tropics (Bonell & Bruijnzeel, 2005; Chaves et al, 2008; Monfreda et al, 2005; van Meerveld et al, 2019; Wohl et al, 2012), but experimental research conducted in undisturbed forested areas is limited (see Zhang et al, 2010 as an exception and a global review by Zimmermann et al, 2012), particularly in humid tropical forests with a geomorphology of volcanic origin (Muñoz‐Villers & McDonnell, 2012; Solano‐Rivera et al, 2019). The natural dynamics of hydrological processes and runoff generation are relatively unknown in humid tropical environments despite some early work that goes back to the late 1970s by Bonell and Gilmour (1978).…”
Section: Introductionmentioning
confidence: 99%
“…"Fallows" were found to be intermediate between forests and grasslands in terms of infiltration in Madagascar [63]. Recovery of infiltration after the reforestation of grasslands in the Philippines was found to be a matter of decades rather than years [64]. In studies elsewhere in Indonesia, forest soils had more macropores and higher surface infiltration rates than monoculture coffee plantations [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, their spatial distribution is presented in the next section. Knowledge about the eco-hydrological functioning of tropical catchments is important due to the provision of important ecosystem services , their high sensitivity to moisture supply from oceanic water bodies (Durán-Quesada, Gimeno, & Amador, 2017;Munksgaard et al, 2015;Sánchez-Murillo et al, 2016), drought periods (Hidalgo, Amador, Alfaro, & Quesada, 2013) and implications of land use change (Evaristo, Jasechko, & McDonnell, 2015;Ochoa-Tocachi et al, 2016;van Meerveld, Zhang, Tripoli, & Bruijnzeel, 2019). Overall STARRtropics, now modified for stream and transpiration water partitioning, facilitates estimation of plant transpiration rates quantifying water age dynamics within the catchment in space and time (McDonnell & Beven, 2014).…”
Section: Simulated Spatio-temporal Transpiration Dynamicsmentioning
confidence: 99%